A Study on Exploitation of Consumer Impulsivity through ‎Marketing Tactics in Bengaluru Supermarkets, Contributing to ‎Unsustainable Consumption Patterns and What Strategies Can ‎Be Implemented to Foster Responsible Consumer Behavior and ‎Environmental Sustainability - A, Ms. Suriya Kumari; Mani, Dr. S; Arumugam, Dr. A; Smitha, Ms. Candida (International Journal of Accounting and Economics Studies, 2025)
This study empirically explored marketing practices used in Bengaluru supermarkets, which leverage consumer impulsive ‎purchasing, making it more brutal and unsustainable consumption. The study presents a conceptualization of supermarket marketing ‎strategies that enable consumers to engage in impulse purchase and then utilizes this framework in the analysis of the literature as well as ‎primary data from structured questionnaires. It examines the relationship between impulse buying and unsustainable consumption patterns, ‎proposing strategies for promoting more responsible consumer behaviors that will benefit environmental sustainability. The methods used ‎for data analysis include Chi-Square tests, Correlation Analysis, and Regression Analysis to the data and uncover actionable insights‎.